Does Urinary Bladder Shape Affect Urinary Flow Rate in Men with Lower Urinary Tract Symptoms? - Yusuf Ziya Ateşçi; Özgü Aydoğdu; Ayhan Karaköse; Mahmut Pekedis; Ömer Karal; Utku Şentürk (The Scientific World Journal)
We aimed to investigate the role of urinary bladder shape which may potentially change with advancing age, increased waist circumference, pelvic ischemia, and loosening of the urachus on bladder emptying and UFR. We retrospectively investigated the medical records of 76 men. The patients were divided into two groups according to bladder shapes in MRI scan (cone and spheric shapes). There was a significant difference between the two groups in terms of IPSS, Qmax, Qave, and waist circumference. A positive correlation has been demonstrated between mean peak urinary flow rate measured with UFM and mean flow rate calculated using the CP. There was a significant difference between mean urinary flow rates calculated with CP of cone and sphere bladder shapes. The change in the bladder shape might be a possible factor for LUTS in men and LUTS may be improved if modifiable factors including increased waist circumference and loosening of the urachus are corrected.